A Study of Role and Duties of Human Resources in Multi-National Corporations - MALVIYA, BINDOO; JAIN, VIBHOR (The journal of contemporary issues in business and government, 2021)
The role of human resources (HR) in an organization is very critical and exploring at the same time. Human resources are the first person who builds a relationship between company and employee. The way HR represents the organization to the company is the same way an employee sees its organization. Various type of companies and organizations works for a different domain but HR department is commonly present in all. In this paper, a brief study is done in the context of the role and duties of HR, a personal interview is conducted for various HR students and employees in different phases. Their responses are being shared in this paper. From a future perspective, various aspects of HR can be analyzed and learned from this by learners & researchers.